Myokines and Resistance Training: A Narrative Review - Zunner, Beate E.M.; Wachsmuth, Nadine B.; Eckstein, Max L.; Scherl, Lukas; Schierbauer, Janis R.; Haupt, Sandra; Stumpf, Christian; Reusch, Laura; Moser, Othmar (International Journal of Molecular Sciences, 2022)
In the last few years, the muscular system has gained attention due to the discovery of the muscle-secretome and its high potency for retaining or regaining health. These cytokines, described as myokines, released by the working muscle, are involved in anti-inflammatory, metabolic and immunological processes. These are able to influence human health in a positive way and are a target of research in metabolic diseases, cancer, neurological diseases, and other non-communicable diseases. Therefore, different types of exercise training were investigated in the last few years to find associations between exercise, myokines and their effects on human health. Particularly, resistance training turned out to be a powerful stimulus to enhance myokine release. As there are different types of resistance training, different myokines are stimulated, depending on the mode of training. This narrative review gives an overview about resistance training and how it can be utilized to stimulate myokine production in order to gain a certain health effect. Finally, the question of why resistance training is an important key regulator in human health will be discussed.
CRIS-Team Scopus Importer:2022-04-01
Keywords: BDNF; IL-6; Irisin; Myokine; Myostatin; PGC-1 alpha; Resistance training